POTENSI MITIGASI EMISI GAS RUMAH KACA DARI KEGIATAN EKSPLORASI DAN PRODUKSI MINYAK DAN GAS BUMI DI PT. XYZ - Agung Ghani Kramawijaya; Kania Dewi (Journal of Environmental Engineering and Waste Management, 2017)
The activity of exploration and production in oil and gas industry is significant greenhouse gas (GHG) emission source. PT. XYZ is one of upstream oil and gas industry in Indonesia and it have large crude oil and gas potential with it reserves that not manage yet. Therefore, GHG emission potential from the activity of exploration and production in PT. XYZ is very large. This study is done for estimate GHG emission reduction potential in PT. XYZ from various activities. Emission inventory is the first step to estimate GHG released to atmosphere. Method of estimation use the method developed by American Petroleum Institute (API). This study considers three types of mitigation measures options, including technical options (scenario 1), behavior option (scenario 2), and policy option (scenario 3). Based on emission inventory, flare and oil storage tank are primary source of GHG emissions in PT. XYZ. Scenario 1 prefers control of GHG emissions in flare and storage tank as primary emission source. While others scenario prefers to control GHG emission from transportation sector. Scenario 1 has potential to reduce emissions by 48.3 %. While scenario 2, and 3 in sequences have potential to reduce emissions by 0.15%, and 0.52%. Emissions flare and oil storage tank can be reduced through the installation of flaring gas recovery unit and vapor recovery unit. Both are effective and efficient in reducing GHG emissions in PT. XYZ. In addition, all mitigation measures of transportation sector provide benefits even though the amount of GHG that can be reduced is not significant.